Web-Based Human Resource System Quality Analysis Using ISO 25010:2011 Method Based on Usability Characteristics - Grace Desi Geoloni; Dewi Agushinta R. (Sistemasi: Jurnal Sistem Informasi, 2023)
The application of information technology is a crucial aspect of Human Resources (HR) activities in an organization (company) to manage its employees, such as attendance data, personal data, and performance appraisals. This data can produce information to make a decision. To assist HR in carrying out their duties, an IT company implements a Human Resources Information System (HRIS), but it has never been tested. The purpose of this research is to test the Human Resource system that has been implemented using the ISO 25010:2011 method with usability characteristics. The research stage starts with analyzing the employees' problems with using the system. Tests are divided into 2 types, namely on employees who often use the system and employees who rarely use the system, and determining the research method. Afterward, determine the characteristics and sub-characteristics and their weight, make assessment indicators of the sub-characteristics, assess the usability characteristic testing, and at the end, total calculation of them. The results showed that the lowest ratings were still obtained for the employee learnability sub-characteristics, namely 77.2% and 65.3% for both types. Therefore, it is recommended that the company should make a detailed user guide and prepare training for all employees. So they will understand the system well.